Pendampingan Manajemen Strategik Peningkatan Mutu Lembaga Di Mts Negeri 6 Cirebon Kota Cirebon - Agus Prayitno; Cecep Supriadi; Alis Tientan Zilah; Rosi Hardianti; Ade Z; Ohin Saeful Rohim (Etos : Jurnal Pengabdian Masyarakat, 2022)
In the implementation of Strategic Management of Islamic Educational Institutions Islamic Educational Institutions in Improving Teacher Quality which is implemented at MTs Negeri 6 Cirebon, it is more focused on achieving the vision, mission, and goals of the madrasa. The scope of the targets/targets to be achieved is also part of the cluster of madrasa strategic management substances which include; curriculum, learning and human resource development. These components are the most important part of the targets which are also implemented in education management in the process of achieving quality education at MTs Negeri 6 Cirebon. The efforts and hard work that are realized jointly between madrasa residents, especially educators (teachers) so that superior madrasa management can be realized both in quantity and quality are realized with various achievements they have. Achievement is a measure of the success of an institution, for that academic and non-academic achievements will be the main goal of this institution at the district, provincial and national levels. In this case, MTs Negeri 6 Cirebon has shown that it is indeed an achiever, this can be proven by a number of achievements made by this institution both at the district and provincial levels. Abstrak Dalam implementasi Manajemen Strategik Lembaga Pendidikan Islam Lembaga Pendidikan Islam Dalam Peningkatan Mutu Guru yang diterapkan di MTs Negeri 6 Cirebon, lebih difokuskan pada pencapaian visi, misi, dan tujuan madrasah. Adapun ruang lingkup dari target/sasaran yang ingin dicapai adalah juga bagian dari gugusan substansi manajemen strategik madrasah yang meliputi; kurikulum, pembelajaran dan pengembangan sumber daya manusia, Komponen-komponen tersebut adalah bagian terpenting dari sasaran yang juga diimplementasikan dalam manajemen pendidikan dalam proses pencapaian pendidikan yang bermutu di MTs Negeri 6 Cirebon. Upaya dan kerja keras yang diwujudkan bersama antara warga madrasah khususnya tenaga pendidik ( guru ) agar dapat terwujud pengelolaan madrasah yang unggul baik secara kuantitas maupun kualitatas terwujud dengan berbagai prestasi-prestasi yang dimilikinya. Prestasi adalah ukuran keberhasilan suatu lembaga, untuk itu prestasi akademik maupun non-akademik akan menjadi tujuan utama lembaga ini baik di tingkat kabupaten, provinsi maupun nasional. Dalam hal ini, MTs Negeri 6 Cirebon telah menunjukkan bahwa dirinya memang berprestasi, hal ini dapat dibuktikan dengan sejumlah prestasi yang diraih lembaga ini baik tingkat kabupaten maupun provinsi